Margaret Lyneis and the Pottery Traditions of Corn Creek and Ash Meadows, Southern Nevada. Issue 4 (2nd October 2019) - Roberts, Heidi; Hagopian, Janet; Ahlstrom, Richard V.N.; Sakai, Sachiko
Abstract : Margaret Lyneis examined pottery recovered from two of southern Nevada's desert oases, the Desert National Wildlife Refuge and the Ash Meadows National Wildlife Refuge. People occupied these rich havens of springs and lush vegetation fairly continuously from the Early Archaic period, with farming practiced during the Formative and Post-Formative periods. Lyneis' investigations demonstrated for the first time that pottery was made in these locations during the later periods, with tempers for both gray and brown ware ceramics consisting of crushed rock obtained from adjacent mountains. This paper summarizes these studies and reflects on the implications of Lyneis' research for understanding Nevada's prehistory.